Cremanthodium magnificum (Asteraceae-Senecioneae), a new species from northern Myanmar - Fei, Wen-Qun; Zhang, Yu; Wang, Long (Phytotaxa, 2019)
Cremanthodium magnificum (Asteraceae-Senecioneae), a new species from northern Myanmar, is described and illustrated. It is somewhat similar to both C. chungdienense and C. pyrolifolium in having robust stature, large-sized leaves and hemispheric involucre. However, C. magnificum differs from C. chungdienense mainly by stem indumentum, leaf shape, capitulum number and synflorescence type. From C. pyrolifolium, C. magnificum is distinct by stem indumentum, leaf shape, capitulum number and ray lamina shape.